Structure of 2-methylisoborneol synthase from Streptomyces coelicolor and implications for the cyclization of a non-canonical C-methylated monoterpenoid substrate() - Köksal, Mustafa (2012)
The crystal structure of 2-methylisoborneol synthase (MIBS) from Streptomyces coelicolor A3(2) has been determined in complex with substrate analogues geranyl-S-thiolodiphosphate and 2-fluorogeranyl diphosphate at 1.80 Å and 1.95 Å resolution, respectively. This terpenoid cyclase catalyzes the cyclization of the naturally-occuring, non-canonical C-methylated isoprenoid substrate, 2-methylgeranyl diphosphate, to form the bicyclic product 2-methylisoborneol, a volatile C(11) homoterpene alcohol with an earthy, musty odor. While MIBS adopts the tertiary structure of a class I terpenoid cyclase, its dimeric quaternary structure differs from that previously observed in dimeric terpenoid cyclases from plants and fungi. The quaternary structure of MIBS is nonetheless similar in some respects to that of dimeric farnesyl diphosphate synthase, which is not a cyclase. The structures of MIBS complexed with substrate analogues provide insights regarding differences in the catalytic mechanism of MIBS and the mechanisms of (+)-bornyl diphosphate synthase and endo-fenchol synthase, plant cyclases that convert geranyl diphosphate into products with closely related bicyclic bornyl skeletons, but distinct structures and stereochemistries.